Sospechosos comunes: los frailes de Veracruz bajo la vigilancia del gobierno federal, 1824-1833 - Carbajal López, David (Revista Complutense de Historia de América, 2008)
The religious orders of the New Spain reached h century affected by important problems deriving from of the secularization of the “doctrinas”, civil war and the liberal revolution. After independence, an important percentage of friars awoke double suspicions because of their Spaniard origin and their opposition to the liberalism. At first, the governmental vigilance was directed only to obtaining information on ecclesiastical authorities, but after the discovery of the conspiracy of Arenas, it began to be build a more extensive network of informers among the civil authorities and even private persons. Most of the “suspects” were expelled between 1828 and 1833. The investigations carried out by the authorities allow us to contemplate the flight of several brothers during the civil war, their ideology and activities, as well as the vision that the liberals of the epoch had of the friars and their conduct.